Potential of non-FDG PET radiotracers for paediatric patients with solid tumours - Leonor Teles; Nelleke Tolboom; Sabine L.A. Plasschaert; Alex J. Poot; Arthur J.A.T. Braat; Max M. van Noesel (EJC Paediatric Oncology)
Molecular imaging with positron emission tomography (PET) offers significant potential for improving diagnostic accuracy, staging and treatment monitoring in paediatric solid tumours, by using radiopharmaceuticals more specific than [18F]fluorodeoxyglucose ([18F]FDG). While non-[18F]FDG tracers have already improved diagnostic abilities in adult solid cancers such as prostate and neuroendocrine tumours, their use in the paediatric population has been underexplored. This narrative review summarises clinical evidence regarding the use, advantages, and limitations of these more specific PET tracers in paediatric patients. In neuroblastoma, [18F]mFBG, [18F]F-DOPA, and SSTR-targeting peptides stand out as the most evolved and promising tracers for the clinical setting, with encouraging results regarding feasibility, safety and detection rates. SSTR-targeting peptides have also consistently outperformed other imaging methods (both conventional and functional) and carry the benefits of theragnostic applications. For brain tumours, amino acid-based tracers in general stand out due to their ability to surpass the blood-brain barrier/blood-tumour barrier (BBB/BTB) and their specific accumulation in malignant tissue. Other paediatric solid tumours, such as sarcoma and bone tumours, suffer from a clear lack of clinical evidence that should be addressed in the near future. The studies performed to date show high accuracy, evident prognostic value, and significant clinical impact of non-[18F]FDG tracers in paediatric patients with solid tumours. However, prospective studies with longer follow-up times are warranted to provide high-level evidence regarding the impact of these tracers on patient management and prognosis, to consolidate the encouraging results obtained so far. Further research and international collaboration will be essential to overcome current challenges related to low incidence of paediatric solid tumours, logistical barriers and concerns about radiation exposure.